Ventromedial Prefrontal Cortex Tracks Multiple Environmental Variables during Search - Mehta, Priyanka S.; Tu, Jiaxin Cindy; LoConte, Giuliana A.; Pesce, Meghan C.; Hayden, Benjamin Y. (The Journal of neuroscience, 2019)
To make efficient foraging decisions, we must combine information about the values of available options with nonvalue information. Some accounts of ventromedial PFC (vmPFC) suggest that it has a narrow role limited to evaluating immediately available options. We examined responses of neurons in area 14 (a putative macaque homolog of human vmPFC) as 2 male macaques performed a novel foraging search task. Although many neurons encoded the values of immediately available offers, they also independently encoded several other variables that influence choice, but that are conceptually distinct from offer value. These variables include average reward rate, number of offers viewed per trial, previous offer values, previous outcome sizes, and the locations of the currently attended offer. We conclude that, rather than serving as specialized economic value center, vmPFC plays a broad role in integrating relevant environmental information to drive foraging decisions. Decision makers must often choose whether to take an immediately available option or continue to search for a better one. We hypothesized that this process, which is integral to foraging theory, leaves neural signatures in the brain region ventromedial PFC. Subjects performed a novel foraging task in which they searched through differently valued options and attempted to balance their reward threshold with various time costs. We found that neurons not only encode the values of immediately available offers, but multiplexed these with environmental variables, including reward rate, number of offers viewed, previous offer values, and spatial information. We conclude that vmPFC plays a rich role in encoding and integrating multiple foraging-related variables during economic decisions.